The Effect of Profitability and Liquidity on the Firm Value in Consumer Goods Companies on the Indonesia Stock Exchange, 2019-2023 - Rifqy Fauzi Abdullah; Hariandy Hasbi (Dinasti Publisher, 2025)
Firm value serves as a crucial indicator in the capital market, representing the level of investor confidence in a company’s long-term growth potential. Within the consumer goods industry, profitability and liquidity play pivotal roles in determining a firm’s investment appeal. This research investigates the influence of profitability and liquidity on the firm value of 30 consumer goods companies listed on the Indonesia Stock Exchange during the period 2019 to2023, resulting in 150 panel data observations. Profitability is measured using Return on Assets, liquidity is proxied by the Current Ratio, and firm value is assessed through Price to Book Value. Employing a quantitative associative approach, the data were processed via multiple linear regression analysis on panel data, with the sample selected through a purposive sampling technique. The results reveal that Return on Assets exerts a positive and statistically significant effect on firm value, whereas the Current Ratio demonstrates a negative yet statistically insignificant impact. Simultaneously, both independent variables jointly exhibit a significant influence on firm value. These findings indicate that investors in the consumer goods sector are more responsive to enhancements in asset utilisation efficiency than to excessive liquidity levels.